Sustainable development : a New Zealand agri-food corporate business and cooperative response : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agribusiness at Massey University, Manawatu, New Zealand - Deterville, Apral Kara (Massey University, 2022)
The United Nation (UN) has commissioned a global call to action a sustainable future through the development and achievement of 17 Sustainable Development Goals (SDGs) by 2030. Corporate business and cooperative business models in the New Zealand Agri-food sector are recognised as key actors in the adoption of the sustainable development agenda to address social, environmental, and economic global challenges. This research seeks to analyse the response to sustainable development between two different business models: Agri-Food corporate business and Agri-Food cooperatives in New Zealand. The main objectives of the study were to develop and apply a theoretical framework in response to sustainable development by two different business models: Agri-Food corporate business and cooperative models, and to compare the responses to sustainable development in these two models. The study was conducted through a multiple case study approach of the two business models within the red meat sector in New Zealand. A qualitative research approach was adopted using a semi-structured interview approach for primary data collection and assessing business documents for secondary data. The participants were selected by purposive sampling to ensure the validity and specific information and insight were captured from relevant actors. A cross-analysis and pattern matching was used to analyse and compare the results of both entities. The results from the study indicated that both business models are responding to economic, environmental, and social dimensions of sustainable development. The analysis revealed that the Agri-Food cooperative is responding to all dimensions but more extensively toward the social dimension of sustainable development. The Agri-Food corporate business is responding to all dimensions but more broadly, responding toward the environmental dimension of sustainable development. As both business models are responding to sustainable development, it is recognised that both firms are in the initial stages of developing a formal approach of reporting sustainability within their organisations, structuring their activities to better align to international sustainable development reporting standards.
Keywords: business models; corporate business; cooperative; sustainable development; 300208 Farm management, rural management and agribusiness